Politikverflechtung in der Entflechtungsfalle: Kooperation im Mehrebenensystem der Europäischen Raumentwicklungspolitik - Graute, Ulrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The pattern of loose coupling is understood as an instrument to avoid the joint decision trap. But how loose a coupling can be without loosing its linkage function? The article follows this question by analysing the case of European Spatial Development Policy which has been developed in the course of the 90s. This new policy field deals with the complex subject of a balanced and sustainable development of the European territory. In spite of the ambitious objectives a respective competence at community level shall not be established. Common goals shall be achieved by voluntary co-operation. The institutional context in the field is marked by a permanent risk of high and unilateral costs of transaction and this in turn presses even actors willingly to co-operate to choose the exit option. The framework of co-operation turns into a new trap, which can block the co-operation process. This can be avoided if actors accept a stronger coupling of their co-operation.